An assessment of the Young Lives sampling approach in Andhra Pradesh, India - Kumra, N (2008)
This paper outlines the sampling methodology used by Young Lives in Andhra Pradesh (India). The Andhra Pradesh team selected study sites with a pro-poor bias using purposive and random sampling approaches. This paper assessed this sampling methodology by comparing baseline data collected in 2002 with data from a nationally representative survey. Examination of the common variables in the different surveys – household characteristics and assets, access to electricity and drinking water – indicates that the Young Lives sample includes households with better access to basic services and more ownership of assets and thus includes some biases. A comparison of wealth index scores reveals that the Young Lives households seem to be slightly wealthier than the average household in Andhra Pradesh. Nevertheless, households in the Young Lives sample are less likely to own their house. These differences could be partly accounted for by the earlier collection year of the nationally representative survey. Despite these biases, it is shown that the Young Lives sample in Andhra Pradesh covers the diversity of children in the country. Therefore, while not suited for simple monitoring of child outcome indicators, the Young Lives sample will be an appropriate and valuable instrument for analysing causal relations, modelling child welfare, and its longitudinal dynamics in Andhra Pradesh.